장애학생 대상 스마트교육 선행연구 분석을 통한 콘텐츠 설계 전략의 탐색적 연구 - 손지영(Ji-Young Son) (디지털콘텐츠학회논문지, 2022)
스마트교육은 신체적, 인지적으로 특별한 요구를 가진 장애학생에게 개별화된 맞춤형 교육을 효과적으로 제공할 수 있는 가능성을 가진다. 이에 본 연구는 장애학생 스마트교육에 대한 국내 선행연구들을 분석하여 스마트교육 콘텐츠 설계 전략을 탐색하는 것을 목적으로 하였다. 연구방법으로 2021년 7월까지 발표된 논문 중, 선정기준에 적합한 54편의 연구들을 분석 대상으로 선정하였고, 선행연구들에서 장애학생에게 적용한 중재 방법이나 설계 전략들을 분석하여 콘텐츠 설계 전략을 도출하였다. 분석 대상 연구들의 연구대상은 학령기의 지적장애 또는 자폐성 장애 학생들이 다수를 차지하였고, 연구설계는 소수의 학생들을 대상으로 하는 단일대상연구 설계를 적용하고 있었다. 연구결과, 장애학생 대상 스마트교육 콘텐츠 설계 전략은 학습 내용 제시 전략, 학생 활동 및 상호작용 전략, 학습 지원 전략의 3가지 영역으로 도출되었다. 이러한 설계 전략들은 향후 장애학생을 위한 효과적인 스마트교육 콘텐츠 개발에 기여할 수 있을 것이다. Smart education has the potential to effectively provide individualized and customized education to students with special needs physically and cognitively. The purpose of this study is to explore the smart education content design strategy for students with disabilities by analyzing previous domestic studies on smart education for students with disabilities. As a research method, among the papers published by July 2021, 54 studies suitable for the criteria were selected for analysis, and content design strategies were derived by analyzing the intervention methods or design strategies applied to students with disabilities. The majority of the research subjects were students with intellectual disabilities or autistic disorders of school age, and the study design was applied to a single-subject design targeting a small number of students. As a result of the study, smart education content design strategy for students with disabilities was derived in three areas: learning content presentation, activity and interaction, and learning support. These design strategies will be able to contribute to the development of effective smart education contents for students with disabilities in the future. KCI Citation Count: 1